Bibliometric Analysis on A Review of Islamic Human Capital - Marlina, Lina (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Human capital has a central role in economic development and physical capital, which affects economic development. On the other hand, human capital tends to have an accumulative and long-term effect compared to physical capital. The accumulation of human capital is expected to be one of the initial sources of sustainable development. The interrelationship between economic growth and human capital growth may be an important key to sustainable economic growth. The development contributes to one aspect, namely economic growth, but can contribute to other aspects such as welfare and poverty reduction. Individual economic success and the overall economy depend on how extensively and effectively people invest in themselves. Technology can be the driving force of the modern economy, especially from the high-tech sector, but human capital is the fuel. This study aims to determine the development of Islamic human capital research trends published by leading journals on Islamic financial economics. The data analyzed consisted of 228 indexed research publications. The data is then processed and analyzed using the VoS viewer application to determine the bibliometric map of Islamic human capital research development